About the validity of the principle of subsidiarity in economic activities in the State - Segovia Olave, Elio (Derecho Público Iberoamericano, 2017)
In this paper, the author enters the debate about the validity of the Principle of Subsidiarity in the Business State Activity in the art. 19 No. 21 of the Constitution. Here presents on one hand the positions that claim it and on the other hand the arguments that deny it, then questions both opinions trying to present their own, to finally seek to solve the underlying problem proposing an interpretation of the text indicated and express their appreciation about the debate.